EFFECT OF EMPLOYEE MORALE ON PRODUCTIVITY IN THE GHANAIAN PUBLIC SECTOR. THE MEDIATING ROLE OF DELEGATION - Aidoo, Eunice (Archives of Business Research, 2018)
Delegation of authority is one of modern trends practiced by managers, and a key management skill in the business world. It enhances human relations amongst organizational members, increases self-confidence among employees and raise the level of tasks accomplishment in tasks. The study sought to assess the effect of delegation on employee morale and productivity in public sector organisations in Ghana. The target population included all the workers in the public sector of Ghana from which the simple random sampling technique was employed to select 128 workers from 20 public sector organisations across the country. The findings from the study show that delegation of authority has a positive and significant relation with employee morale and productivity. Subsequently, the study also revealed that delegation fully mediates the relationship between employee morale and productivity. Based on the findings, it is recommended that organisations should utilise or adopt the concept of delegation in performing organisational duties. Again, organisations should implement measures or strategies that can help build the morale of employees.